ANALYSIS OF THE USE OF ACRYLIC WASTE AS A PARTIAL SUBSTITUTION OF COARSE AGGREGATE FOR CONCRETE COMPRESSIVE STRENGTH - DEDY RAMADHAN; ACHMAD PAHRUL RODJI; INDRIASARI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
Acrylic, or polymethyl methacrylate, is a synthetic polymer that has superior properties compared to glass, such as flexibility, light weight, easy to process (cut, drill, polish), and can be formed into various complex shapes through thermal processes. This material has advantages in resistance to impact and weather conditions, and is environmentally friendly because it can be recycled. Acrylic is widely used in industries, including advertising, automotive, and interior design, due to its ease of processing and aesthetics. However, the production of acrylic products is still considered inefficient and expensive, triggering the need for new tools for the bending process to increase the efficiency of making acrylic-based products. Based on the results of the average concrete compressive strength test for normal concrete at the age of 28 days is 11.94 Mpa, the compressive strength results are less than the planned concrete quality of 25 Mpa; Based on the research results, it was found that concrete using acrylic waste as a partial replacement for coarse aggregate at the age of 28 days at a variation of 3% was 13.94 MPa, a variation of 5% was 24.87 MPa and a variation of 7% was 7.97 MPa, so it can be concluded that the more acrylic waste mixture for the compressive strength of concrete, the results will decrease.